Peran Otonomi Daerah dalam Meningkatkan Kualitas Pendidikan Melalui Desentralisasi - Elisa Wulandari; Qolby, Hafshoh Robi’a; Devi, Irena Sinta; Azis, Abdul (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Education is the main foundation in creating quality human resources, but until now the quality of education in Indonesia still faces serious challenges, especially in terms of inequality in the distribution of resources between urban and rural environments. This study aims to examine the role of regional autonomy in improving the quality of education in Indonesia within the framework of decentralization. The approach used in this study is qualitative descriptive with a literature study method. Data collection techniques are carried out through literature reviews from books, scientific journals, and education policy documents, which are then analyzed critically to explore the relationship between decentralization policies and improving the quality of education. The results of the study indicate that regional autonomy allows for more contextual education policies that are in accordance with local needs, so that they can significantly improve the quality of education. However, challenges such as disparities in resources between regions, budget constraints, and lack of readiness of regional apparatus are still major obstacles. This study concludes that the success of educational decentralization is highly dependent on managerial readiness, policy commitment, and technology integration and community participation in the education process.